Study on Correlation of Carotid Artery Intima–Media Thickness and Dyslipidemia in Chronic Kidney Disease in a Bangladeshi Population - Mohammad Kaiser, Amir; Islam, Rafi Nazrul; Mozaffor, Miliva; Feroz, Salahuddin; Rahman, Md Mustafizur (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: In chronic kidney disease (CKD) patients,measuring carotid artery intima– media thickness (CIMT) canpredict coronary heart disease and stroke, resulting from systemic atherosclerosis. Objective: To find out correlation of carotid artery intima–media thickness and dyslipidemia in chronic kidney disease in a Bangladesh population. Methods: A cross-sectional analytic study was conducted in the Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladeshi, between July 2014 and June 2015, on 80 CKD patients. Standard laboratory techniques were followed to estimate all biochemical parameters. CIMT measurement was done by duplex study of carotid vessels through high resolution B-mode ultrasound technique. Results: Among 80 patients, 29 (36%) were in 18-30 age group, 18 were (23%) 31-40 age group and 33 (41%) were between 41-50 age group; mean age was 36.1±9.5 years. 51 (64%) patients were male and 29 (36%) were female. Though mean CIMT was found markedly increased in all CKD patients, the differences among stage 3, 4 and 5 was not significant. Mean CIMT was found more in dyslipidemic patients in comparison those with normal lipid profile, which was statistically significant (p<0.05). Positive correlations were found between total cholesterol (TC) and CIMT (r=+0.295; p=0.008), triglyceride (TG) and CIMT (r=+0.238; p=0.034), and lowdensity lipoprotein (LDL) and CIMT (r=+0.231; p=0.039). However, there was negative correlation between high-density lipoprotein (HDL) and CIMT (r=–0.242; p=0.030). Conclusion: Our data suggest that the mean carotid intima-media thickness was markedly high in patients with CKD in comparison to normal expected value; however, there was no significant difference in thickness among CKD stages 3, 4 and 5. It was also observed that carotid artery intima-media thickness showed significant positive correlation with total cholesterol, triglyceride and LDL, but negative correlation with HDL. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 271-276